Novel approach to identifying the hepatitis B virus pre-S deletions associated with hepatocellular carcinoma - Zhao, Zhi-Mei (Baishideng Publishing Group Inc, 2014)
AIM: To develop a novel non-sequencing method for the detection of hepatitis B virus (HBV) pre-S deletion mutants in HBV carriers. METHODS: The entire region of HBV pre-S1 and pre-S2 was amplified by polymerase chain reaction (PCR). The size of PCR products was subsequently determined by capillary gel electrophoresis (CGE). CGE were carried out in a PACE-MDQ instrument equipped with a UV detector set at 254 nm. The samples were separated in 50 μm ID eCAP Neutral Coated Capillaries using a voltage of 6 kV for 30 min. Data acquisition and analysis were performed using the 32 Karat Software. A total of 114 DNA clones containing different sizes of the HBV pre-S gene were used to determine the accuracy of the CGE method. One hundred and fifty seven hepatocellular carcinoma (HCC) and 160 non-HCC patients were recruited into the study to assess the association between HBV pre-S deletion and HCC by using the newly-established CGE method. Nine HCC cases with HBV pre-S deletion at the diagnosis year were selected to conduct a longitudinal observation using serial serum samples collected 2-9 years prior to HCC diagnosis. RESULTS: CGE allowed the separation of PCR products differing in size > 3 bp and was able to identify 10% of the deleted DNA in a background of wild-type DNA. The accuracy rate of CGE-based analysis was 99.1% compared with the clone sequencing results. Using this assay, pre-S deletion was more frequently found in HCC patients than in non-HCC controls (47.1% vs 28.1%, P < 0.001). Interestingly, the increased risk of HCC was mainly contributed by the short deletion of pre-S. While the deletion ≤ 99 bp was associated with a 2.971-fold increased risk of HCC (95%CI: 1.723-5.122, P < 0.001), large deletion (> 99 bp) did not show any association with HCC (P = 0.918, OR = 0.966, 95%CI: 0.501-1.863). Of the 9 patients who carried pre-S deletions at the stage of HCC, 88.9% (8/9) had deletions 2-5 years prior to HCC, while only 44.4%4 (4/9) contained such deletions 6-9 years prior to HCC. CONCLUSION: CGE is a sensitive approach for HBV pre-S deletion analysis. Pre-S deletion, especially for short DNA fragment deletion, is a useful predictive marker for HCC.